Intensity-Duration-Frequency (IDF) Curve and the Most Suitable Method to Determine Flood Peak Discharge in Upper Werba Sub-Watershed - Cilcia Kusumastuti; Prasetio Sudjarwo; Marvin Christhie; Timotius Krisna (Institute of Research and Community Outreach - Petra Christian University, 2019)
Design flood is one of the important factors for flood risk assessment and water infrastructures planning and development in a certain location. There are several methods to estimate it, one method which has been commonly and widely use is using flood frequency analysis. This research aims to develop Intensity-Duration-Frequency (IDF) curves in Upper Werba Sub-Watershed, West Papua Province, Indonesia, to estimate design rainfall intensity. The design rainfall intensity is used to estimate peak of flood discharge using Rational Formula in the sub-watershed. Other methods, i.e. Soil Conservation Service and Nakayasu Synthetic Unit Hydrograph are also presented in this paper to provide comparison of the estimated peak of flood discharge. The result shows that the Rational method provide the closest magnitude of estimated flood discharge in Upper Werba Sub-Watershed to the observed streamflow. Therefore, it is suggested that the Rational method can be used for water infrastructure planning and development in the sub-watershed.